Effective elastic properties of lattice materials with intrinsic stresses. (April 2022) - Sinha, P.; Mukhopadhyay, T.
Abstract: Characterization of the effective elastic properties of lattice-type materials is essential for adopting such artificial microstructures in various multi-functional mechanical systems across varying length-scales with the requirement of adequate structural performances. Even though the recent advancements in manufacturing have enabled large-scale production of the complex lattice microstructures, it simultaneously brings along different aspects of manufacturing irregularity into the system. One of the most prevailing such effects is the presence of intrinsic residual stresses, which can significantly influence the effective elastic properties. Here we have proposed closed-form analytical expressions for the effective elastic moduli of lattice materials considering the influence of residual stresses. Besides characterization of the effect of manufacturing irregularities, the presence of such prestress could be viewed from a different perspective. From the materials innovation viewpoint, this essentially expands the design space for property modulation significantly. The proposed analytical framework is directly useful for both property characterization and materials development aspects. The numerical results reveal that the presence of residual stresses, along with the compound effect of other sensitive factors, could influence the effective elastic moduli of lattices significantly, leading to the realization of its importance and prospective exploitation of the expanded design space for inclusive materials innovation. Highlights: Closed-form expressions for elastic moduli of lattices are proposed considering the effect of residual stresses. Characterization of residual stresses would lead to a better understanding of manufacturing irregularities in complex microstructures. From the materials innovation viewpoint, the presence of intrinsic stresses essentially expands the design scope for property modulation. Based on the analytical formulae, the concept of anisotropy tailoring is demonstrated in an expanded design space. A quantification of sensitivity for different microstructural parameters is presented including intrinsic stress.